THE ANALYSIS OF STUDENTS’ NEEDS OF ENGLISH MATERIAL AT SMAN 8 SIDRAP - Latif, Ismail; Sulistiawati, Indah (JURNAL ILMU BUDAYA, 2023)
This study analyzed the students’ needs for English teaching materials which boost the development of their needs for English speaking competence. The research respondents were students of Senior High School 8 in Sidrap Regency.   The findings indicated that 1) students’ needs were having the skill to communicate in English and good preparation of English speaking skills to join the competition of job seeking (target needs), the need for English teaching materials in games and group work (learning needs). 2) Related to the teaching materials expected to meet students’ needs of learning English, some points were found fulfilled: 1) ability to communicate in English and to prepare students to compete in job seeking, 2) assist students to improve English speaking skills, 3) teaching materials from textbooks, social media, and games, and 4) contribution of teaching materials to students’ lack of speaking ability dues to the lack of vocabulary and good pronunciation.